VIOLENCE AGAINST STUDENTS: RESULTS OF THE RESEARCH CONDUCTED AT THE FACULTY OF LAW, UNIVERSITY OF KRAGUJEVAC - Stanisavljevic, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Violence against students is a current problem and its consequences negatively affect not only the individual but also the academic community and society as a whole. Psychological, physical, and sexual violence are the most common forms of this type of violence. The subject of this paper is the presentation of the research results on violence against students, which was conducted in 2023 at the Faculty of Law in Kragujevac and whose sample consisted of 303 students of this faculty. The research aimed to obtain information on whether students at the faculty are exposed to violence, and if so, what form it takes and who its perpetrators are. The results were compared with previous studies on this topic and show that violence at the university is represented on a smaller scale than in previous years, but that there is a worrying percentage of cases in which students did not report the violence they experienced to anyone. The paper presents the views of the respondents on whether the faculty responds adequately to violence against students, as well as the reasons why this type of violence is most often not reported.